Daluwarsa of Criminal Prosecution is Associated The Criminal Threats - ifrani ifrani; Mohammad Rezki Ramadhan Mahfi; Muhammad Topan; Muhammad Hendri Yanova (Faculty of Law, Universitas Pekalongan, 2022)
The purpose of this study is to find out what is the rationale for the existence of a criminal prosecution and to examine future arrangements for a shorter Daluwarsa period than criminal penalties. This research is normative legal research by examining laws related to the legal issues under study and by moving from the views and doctrines that have developed in the science of law related to the problems in this research. According to the results of this study, it shows that: First, the rationale for the existence of a Daluwarsa on criminal prosecution which underlies the legislators to make a policy in this field is none other than legal certainty. This legal certainty is for the sake of creating legal order, namely legal order in the settlement of a criminal case that does not find a bright spot for a long time so that the case does not have a clear direction in its resolution. Second, the current criminal prosecution Daluwarsa policy in several of its provisions in determining Daluwarsa does not pay attention to factors that can support the functioning and operation of criminal law. In several provisions regarding the expiration date for criminal prosecution in several criminal offenses, the Daluwarsa date is shorter than the criminal penalty. The expiry period for criminal prosecution which is shorter than the criminal threat can result in motivating the perpetrators of criminal acts to run away/run away or disappear to avoid legal proceedings against avoiding criminal responsibility.